The Stories of the Core Group facilitators of the Care Group Ministry in the National Cathedral-Iglesia Filipina Independiente - Cutamora, Emelyn Samonte
"One of the challenging aspects of a church is how to make all the existing programs, missions, and ministries relevant to the congregation. Every member is encouraged to participate and to exercise their ministry. Their participation will serve as evidence of their commitment, support, and understanding of the life and work of the church."-- 1st paragraph, Context of the Study
A Thesis Presented to the Faculty of Saint Andrew's Theological Seminary, Quezon City, Philippines
In Partial Fulfillment of the Requirements for the Degree Master in Divinity
Thesis (M.Div.)-- Saint Andrew's Theological Seminary
Includes bibliographical references and index.